Immunogenic Cell Death and Role of Nanomaterials Serving as Therapeutic Vaccine for Personalized Cancer Immunotherapy - Catanzaro, Elena; Feron, Olivier; Skirtach, André G.; Krysko, Dmitri V. (Frontiers in Immunology, 2022)
Immunogenic cell death (ICD) is a rapidly growing research area representing one of the emerging therapeutic strategies of cancer immunotherapy. ICD is an umbrella term covering several cell death modalities including apoptosis, necroptosis, ferroptosis and pyroptosis, and is the product of a balanced combination of adjuvanticity (damage-associated molecular patterns and chemokines/cytokines) and antigenicity (tumour associated antigens). Only a limited number of anti-cancer therapies are available to induce ICD in experimental cancer therapies and even much less is available for clinical use. To overcome this limitation, nanomaterials can be used to increase the immunogenicity of cancer cells killed by anti-cancer therapy, which in themselves are not necessarily immunogenic. In this review, we outline the current state of knowledge of ICD modalities and discuss achievements in using nanomaterials to increase the immunogenicity of dying cancer cells. The emerging trends in modulating the immunogenicity of dying cancer cells in experimental and translational cancer therapies and the challenges facing them are described. In conclusion, nanomaterials are expected to drive further progress in their use to increase efficacy of anti-cancer therapy based on ICD induction and in the future, it is necessary to validate these strategies in clinical settings, which will be a challenging research area.